2019
DOI: 10.1101/517714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delta/Notch signaling controls neuroepithelial morphogenesis in the zebrafish spinal cord

Abstract: The morphogenesis of the nervous system requires coordinating the specification and differentiation of neural precursor cells, the establishment of neuroepithelial tissue architecture and the execution of specific cellular movements. How these aspects of neural development are linked is incompletely understood. Here we inactivate a major regulator of embryonic neurogenesis -the Delta/Notch pathway -and analyze the effect on zebrafish central nervous system morphogenesis. While some parts of the nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The latter links the activation energy needed to recruit additional neighbors with geometrical descriptors (i.e., tissue thickness/curvature). Our results provide new biological insight into the spatiotemporal regulation of cell-cell connectivity, a property that ultimately regulates juxtracrine signaling and is pivotal for primordia patterning and cell fate determination (Sharma et al, 2019;Tung et al, 2012). In this context, our study points towards an effect of scutoids on the regulation of the physiological properties of tissues.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The latter links the activation energy needed to recruit additional neighbors with geometrical descriptors (i.e., tissue thickness/curvature). Our results provide new biological insight into the spatiotemporal regulation of cell-cell connectivity, a property that ultimately regulates juxtracrine signaling and is pivotal for primordia patterning and cell fate determination (Sharma et al, 2019;Tung et al, 2012). In this context, our study points towards an effect of scutoids on the regulation of the physiological properties of tissues.…”
Section: Discussionmentioning
confidence: 67%
“…This formula implies that polygonal cells in packed tissues, on average, have six neighbors (i.e., the average 2D cellular connectivity reads ‫݊ۃ‬ ଶ ‫ۄ‬ ൌ 6). As for its biological consequences, the degree of cellular connectivity determines, for example, the strength of the cell-cell juxtracrine signaling (Tung et al, 2012;Sharma et al, 2019;Perrimon et al, 2012). Not surprisingly, the validity of this connectivity principle to the third dimension has been taken for granted since the role played by apico-basal cell intercalations has been disregarded and cells have been assumed to have prismatic-like shapes in either planar or bent epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…As for the broader implications of our findings, our results provide new biological insight into the regulation of cell-cell connectivity in curved tissues. This property ultimately regulates juxtracrine signaling, and is pivotal for early development, primordia patterning, and cell fate determination (Guignard et al, 2020; Sharma et al, 2019; Tung et al, 2012). Moreover, recent research has shown that cellular connectivity regulates the viscosity of tissues (Petridou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This principle states that polygonal 17 cells in packed tissues, on average, have six neighbors (i.e., the average 2D ). As for its biological consequences, the 19 degree of cellular connectivity determines, for example, the strength of the 20 cell-cell juxtracrine signaling (Tung et al, 2012;Sharma et al, 2019;Perrimon 21 et al, 2012). Not surprisingly, the validity of this connectivity principle to the 22 third dimension has been taken for granted since the role played by apico-23 basal cell intercalations has been disregarded and cells have been assumed 24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation